An Analysis of Students’ English Learning Demotivation at SMKN 7 Takalar - Emiastia, Emiastia; Jabu, Baso; Talib, Ahmad (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This study focuses on analyzing the problems of demotivation that occured in students at SMKN 7 Takalar when learning English and how their teachers overcame the demotivation. The objectives of this study were to find out what causes students to experience demotivation when learning English and how teachers overcame these problems. The method used is descriptive qualitative which using interview instruments involving seven students from class XI majoring in Machinery and two English teachers. Then the seven students were interviewed to find out what causes them to experience demotivation when learning English and the two teachers were also interviewed to find out how they overcame demotivation in students when learning English. The results of the study show that there are several things that cause students to experience demotivation, namely intrinsic and extrinsic problems of students and the lack of positive and negative reinforcement from teachers in the classroom when learning English. As for how teachers overcome these problems, namely by using learning methods that are in accordance with the times and trying as much as possible to adjust the wishes of students.